2003
DOI: 10.1159/000071243
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Endothelin on Bladder Contraction: Potential Role in Bladder Hyperactivity

Abstract: In the present study, we demonstrate that the intravenous infusion of endothelin-1 (3 and 10 ng/kg/min) causes a decrease in the mean micturition volume of rats in addition to an increase in mean arterial pressure. These effects are blocked by both the ETA/ETB-non-selective and the ETA-selective endothelin antagonists SB 217242 and SB 247083 respectively (both 30 mg/kg). However, it was also observed that the ETB-selective agonist sarafotoxin 6c (3 and 10 ng/kg/min) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 10 publications
(10 reference statements)
1
12
0
Order By: Relevance
“…Subsequent studies show that this strain of rats also has significant urological complications demonstrated as development of microscopic kidney stones and bladder calculi [3], hyperactive voiding [4, 5], a shorter filling phase and greater frequency of intravesical pressure rises [6]. SHR often shows an increase in voiding frequency and a decrease in bladder capacity and micturition volume [4, 7].…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent studies show that this strain of rats also has significant urological complications demonstrated as development of microscopic kidney stones and bladder calculi [3], hyperactive voiding [4, 5], a shorter filling phase and greater frequency of intravesical pressure rises [6]. SHR often shows an increase in voiding frequency and a decrease in bladder capacity and micturition volume [4, 7].…”
Section: Introductionmentioning
confidence: 99%
“…ET-1 is synthesized not only by smooth muscle cells in the urinary bladder, but also by epithelial cells and fibroblasts (2). Furthermore, the intravenous infusion of ET-1 was shown to cause a decrease in the mean micturition volume of rats in addition to an increase in mean arterial pressure (16 effects on various urinary dysfunctions including benign prostatic hyperplasia (17). The protective effect of an endothelin-converting enzyme inhibitor on rat detrusor function after outlet obstruction has also been demonstrated (18).…”
Section: Introductionmentioning
confidence: 99%
“…These studies clearly indicate the existence of functional receptors for endothelins in the bladder, which could be a promising target for the treatment of lower urinary tract symptoms. Bladder endothelin receptors have been briefly identified (3,15,16,19,20). However, bladder ET-1 receptor binding of endothelinreceptor antagonists used for the treatment of pulmonary arterial hypertension has not been examined in detail.…”
Section: Introductionmentioning
confidence: 99%
“…I.v. ET-1 is able to decrease the micturition volume, an effect that could be blocked by ET-receptor antagonists [47]. The selective ET-A-antagonist, LU 302146, reduced the stimulation-induced pig bladder contraction in an atropine-inhibited way [48].…”
Section: Neuropeptidergic Systemmentioning
confidence: 99%